Application of artificial intelligence (AI) in islamic investments - Haneffa Muchlis Gazali; Junisa Jumadi; Noor Rasyidah Ramlan; Nurmaisarah Abd Rahmat; Siti Nor Hazilawati Mohd Uzair; Amirah Norliyana Mohid (International Islamic University Malaysia, 2020)
This study examines the application of Artificial Intelligence (AI) in Islamic Investments. AI technology is very popular in both the conventional and Islamic banking systems as reflected in the contributions of AI in Islamic investment. The technology helps investors to analyse their stocks in terms of price levels, the current stability of each stock and the future price forecasts based on current price and stock data. The study is a conceptual discussion on the application of AI in Islamic investment, which focuses on the discussion of Text Mining, Algorithmic Trading, Stock Pick and Robo in Investment, which include Robo Advisor, Robo Islamic Advisor (RIA) and Robo Financial Advisor (RFA) operating in Islamic investment system. Thus, the discussion dwells on the cognitive application along with investment and compliance sectors of the financial services industry. The conclusion of the study highlights the implications, limitations and future research of the subject matter.